Clinical experience of paediatric self-expanding foam cuffed tracheostomy tubes. (December 2021) - Carter, A.; Hall, A.; Thorpe, V.; Cochrane, L.; Cooke, J.
Abstract: Introduction: Use of self-expanding foam-filled tracheostomy tube cuffs (Bivona® FOME cuf®) in paediatrics has become a recent practice within our institution for patients with intractable aspiration. The current literature, clinical indications and subsequent management is lacking. We present our experience with a cohort of children with a foam-cuffed tracheostomy tube managed at Great Ormond Street Hospital, describing their indications and outcomes, as well as routine and emergency management. Method: Our tracheostomy patient population was reviewed and those with a Bivona® FOME cuf® tracheostomy tube were identified and reviewed. The indications for foam-cuffed tracheostomy tube insertion, progress, and further management, including emergency care, were reviewed. Results: Ten patients were identified, all with a chronic history of respiratory infections secondary to aspiration being the leading indication. All patients had an ongoing improvement in their chest function following insertion with no episodes of cuff trauma. One patient had difficulty when a port line was accidently cut, which resulted in difficulty of removal, and we outline a strategy for dealing with this. Conclusion: The foam-cuffed tracheostomy tube is a useful tracheostomy tube to use in the management of chronic aspiration in children with poor chest health, however due to the lack of knowledge and experience they can prove to be a difficult tube to manage. Further educational information should be available as to the indications, routine care and emergency management of Bivona® FOME cuf® tracheostomy tubes. We believe they represent a useful option for institutions to consider in the paediatric population.